Ras subfamily GTPases regulate development, aflatoxin biosynthesis and pathogenicity in the fungus Aspergillus flavus. (14th June 2021) - Zhu, Zhuo; Ma, Gengli; Yang, Mingkun; Tan, Can; Yang, Guang; Wang, Sen; Li, Na; Ge, Feng; Wang, Shihua
Summary: Ras subfamily proteins are molecular switches in signal transduction pathways of many eukaryotes that regulate a variety of cellular processes. Here, the Ras subfamily, encoded by six genes, was identified in Aspergillus flavus : rasA, rasB, rasC, rab‐33, rheb and rsr1 . The rsr1 deletion mutant (∆ rsr1 ), rheb deletion mutant (∆ rheb ) and double deletion mutant (∆ rheb/rsr1 ) displayed significantly decreased growth and sporulation. Sclerotia formation was significantly decreased for ∆ rheb or ∆ rheb/rsr1 but increased for ∆ rsr1 . Aflatoxin production was significantly increased in ∆ rheb but decreased in ∆ rsr1 and ∆ rheb/rsr1 . We found that rsr1 and rheb are crucial for the pathogenicity of A . flavus . Quantitative proteomics identified 520 differentially expressed proteins (DEPs) for the ∆ rsr1 mutant and 133 DEPs for the ∆ rheb mutant. These DEPs were annotated in multiple biological processes and KEGG pathways in A . flavus . Importantly, we identified the cytokinesis protein SepA in the protein–protein interaction network of rsr1, and deletion mutants showed that SepA has pleiotropic effects on growth and AF biosynthesis, which may depend on Rsr1 for regulation in A . flavus . Our results indicated that these Ras subfamily proteins exhibited functional redundancy with each other but there were also differences in A . flavus .